Progressive Failure Analysis of Pin-Loaded Unidirectional Carbon-Epoxy Laminated Composites - Turan, Kadir; Gur, Mustafa; Kaman, Mete Onur (Taylor & Francis Inc, 2014)
In this study, a research was carried out to determine the failure modes and failure loads at pinned joint unidirectional laminated carbon/epoxy composite plates. To evaluate the effects of joint geometry and fiber orientation on the failure loads and failure modes, parametric studies were performed experimentally and numerically. A numerical study was performed by using 3D APDL codes with ANSYS fem software and Hashin Failure Criteria was used for predicted failure mode and failure load. The experimental and numerical results showed that the failure loads of composite plates were increased with increasing E/D and W/D ratios.
Keywords: progressive failure analysis; Hashin Failure Criteria; pin loaded composite; finite element analysis; fiber reinforced composites